Implementasi Neural Network untuk Pembuatan Chatbot Menggunakan Dataset Pertanyaan Mahasiswa - Imanuel Ruben (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research develops a machine learning model for chatbot and chatbot applications. Chatbot is an area of application of Machine Learning and Natural Language Processing. Modelling is done by using the Deep Learning algorithm. The training data used for training is obtained by observation in the student manual of Kalbis Institute. The model created produces an accuracy of 98% and loss value of 0.05275. The model created was tested in the form of a chatbot application by giving various questions relating to topic in the student manual of Kalbis Institute.